2018
DOI: 10.1002/ppul.24006
|View full text |Cite
|
Sign up to set email alerts
|

High frequency oscillatory ventilation in a cohort of children with respiratory failure

Abstract: In this cohort of patients, use of HFOV for pediatric respiratory failure demonstrated a mortality rate in keeping with published data. The presence of an immunocompromised condition was a risk factor for mortality in severe respiratory failure with SCT recipients having the lowest survival rate. The OI at 24 h was the best predictor of mortality, especially in immunocompromised and SCT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In our neonate population suffering from a congenital diaphragmatic hernia, the survival rate at NICU discharge was consistent with previous published studies, 17 suggesting that there was no additional mortality related to the transportation. In our pediatric population, the survival rate was similar to that reported in a recent study which reported similar OI as in our study (56% vs. 58%) 18 . These results demonstrate the feasibility and the safety of HFOV transportations with a trained PICU‐TT, despite some inherent challenges.…”
Section: Discussionsupporting
confidence: 90%
“…In our neonate population suffering from a congenital diaphragmatic hernia, the survival rate at NICU discharge was consistent with previous published studies, 17 suggesting that there was no additional mortality related to the transportation. In our pediatric population, the survival rate was similar to that reported in a recent study which reported similar OI as in our study (56% vs. 58%) 18 . These results demonstrate the feasibility and the safety of HFOV transportations with a trained PICU‐TT, despite some inherent challenges.…”
Section: Discussionsupporting
confidence: 90%
“…Since PALICC, many studies have corroborated the impact of previously identified comorbidities—most notably immunodeficiency (1–21)—and PARDS triggers (22–81) on severity of PARDS or PARDS outcomes. It remains clear that both comorbidities and the many conditions that cause PARDS contribute to the heterogeneity seen in this syndrome.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, there has yet to be an effective pharmacologic treatment for PARDS, and care is supportive. In addition, PARDS is a heterogeneous condition due in part to differences among children in the underlying pathobiology, age (which impacts changes in the lungs, chest wall, and immune system associated with development), comorbidities (1–21), and inciting trigger (22–85).…”
mentioning
confidence: 99%
“…Moreover, our study showed a higher mortality in patient with hematological malignancies. The higher mortality when using HFOV for refractory hypoxemia associated with malignancies and in post-stem cell transplant cases has been described by more than one recent publication [13,14]. These cases deserve the highest degree of vigilance and need additional well-designed trials to account for all possible confounding variables.…”
Section: Discussionmentioning
confidence: 99%